Interferon-α-Induced Changes to Natural Killer Cells Are Associated with the Treatment Outcomes in Patients with HCV Infections. (13th August 2013) - Shimoda, Shinji; Sumida, Kosuke; Iwasaka, Sho; Hisamoto, Satomi; Tanimoto, Hironori; Nomura, Hideyuki; Dohmen, Kazufumi; Takahashi, Kazuhiro; Kawano, Akira; Ogawa, Eiichi; Furusyo, Norihiro; Akashi, Koichi; et al.
Abstract : Aim . We analyzed the pretreatment natural killer (NK) cell functions with the aim of predicting the sustained virological response (SVR) or the interleukin (IL) 28B polymorphism that is strongly associated with the treatment response. Methods . The peripheral NK cells from chronic hepatitis patients with HCV genotype 1 and high virus titers were activated using a Toll-like receptor (TLR) 4 ligand and IFN- α . The cell surface markers were evaluated using a flow cytometric analysis, and IFN- γ production was evaluated using an enzyme-linked immunosorbent assay (ELISA). The genotyping of the polymorphisms in the IL28B gene region (rs8099917) on chromosome 19 was performed on the DNA collected from each patient. Results . The production of IFN- γ was significantly higher in the SVR patients compared with the no-response (NR) patients, whereas the cell surface markers were similar between the SVR and the NR patients. There were no significant differences found in the IL28B genotype distribution associated with the production of IFN- γ . Conclusion . Differences in the NK cell functions were observed between the SVR patients and the NR patients, suggesting that NK cells play a potential role in the treatment response independent of the IL28B genotype.